Perancangan Ide Bisnis Custom Aksesoris Bayi - Isabela -; Hutomo Setia Budi (Universitas Ciputra Surabaya, 2018)
This study focuses on the relationship between visual communication design work and entrepreneurship development with the aim to design a custom business that match with the desire of the the target market through the field of entrepreneurship study and visual communication design. This research was conducted by quantitative method by distributing questionnaires to 100 respondents and qualitative methods through interviews with 5 speakers. This research is also supported by literature studies. Based on research that has been done that custom service is now a trend today because consumers today, much more expressive. Then through a study of literature that is done in the find also that custom enthusiasts more. Business services custom baby accessories has a target market at mothers aged from 23 to 26 years who have children aged 1-5 years. Based on the positive response obtained in the study, this business has an opportunity.